Absence of Adolescent Obesity in Grenada: Is This a Generational Effect? - Scribner, Richard A.; Radix, Roger L.; Gilliland, Aubrey E.; Leonardi, Claudia; Ferguson, Tekeda F.; Noel, Trevor P.; Andall, Rebecca G.; Andall, Naomi R.; Radix, Christal; Frank, Rhoda; Benjamin, Jonell; James, Jenifer; et al. (Frontiers in Public Health, 2018)
Objective: Low- and middle-income countries are affected disproportionately by the ongoing global obesity pandemic, for which ultra-processed foods have largely been attributed as a main contributor. As a low-income country, Grenada’s increased prevalence of obesity may coincide with the introduction of processed foods in the 2000s. The objective of this study was to characterize the prevalence of obesity among Grenadian adolescents and to determine if this population is experiencing an increased risk compared to their US counterparts alongside Grenadian adults. Methods: Using a subcohort of participants in the Grenadian Nutrition Student Survey, a food frequency questionnaire and anthropometric measures were collected from 55% of the classrooms of first year secondary students in Grenada (n=639). Rural or urban designations were given to each school. Body Mass Index (BMI) was calculated for each student, with BMI scores greater than 85th percentile classified as overweight and BMI scores over 95th percentile classified as obese, and a standardized BMI (BMIz) was calculated for each school. Multilevel models of students nested within schools were conducted to determine if BMIz differed by rural or urban locality. Results: The mean age of this cohort was 12.7 (SD=0.8) years with 83.8% of the cohort identifying as Afro-Caribbean. Grenadian adolescents had lower rates of overweight (females: 22.7% vs. 44.7%; males: 12.2% vs. 38.8%, respectively) and obesity (females: 8.2% vs. 26.1%; males: 6.8% vs. 25.4%, respectively) as compared to US counterparts. Females had nearly twice the prevalence of overweight when compared to males (22.7% vs. 12.2%) but a similar prevalence of obesity (8.2% versus 6.8%). Eating a traditional diet was negatively associated with BMIz score among the girls (β ̂= -0.395; SE=0.123) in a stratified, multilevel analysis. Conclusions: The study identified decreased prevalence of overweight and obesity in Grenadian adolescents compared with both their US counterparts and Grenadian adults. Adherence to a diet of traditional prepared foods was associated with lower BMIz scores among the females. Further research is needed in this population to determine whether a generational effect of increasing adolescent obesity will be observed in subsequent birth cohorts.